2007
DOI: 10.1002/prot.21432
|View full text |Cite
|
Sign up to set email alerts
|

Multiple asparagine deamidation of Bacillus anthracis protective antigen causes charge isoforms whose complexity correlates with reduced biological activity

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
42
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 81 publications
3
42
0
Order By: Relevance
“…These studies have reported loss of stability, activity of proteins, and also increased aggregation properties as shown in crystallins, 7,8,11,12,23,24,[51][52][53] superoxide dismutase, 49 and immunoglobins. 14,34,54 Reported properties of mutC suggest that this protein has retained the secondary and tertiary structure with a partial loss in activity but with a significant improvement in the ability to withstand multiple heat cycles.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have reported loss of stability, activity of proteins, and also increased aggregation properties as shown in crystallins, 7,8,11,12,23,24,[51][52][53] superoxide dismutase, 49 and immunoglobins. 14,34,54 Reported properties of mutC suggest that this protein has retained the secondary and tertiary structure with a partial loss in activity but with a significant improvement in the ability to withstand multiple heat cycles.…”
Section: Discussionmentioning
confidence: 99%
“…While deamidation of Asn residues in rPA has been demonstrated, little is known about the effect that deamidation might have on the immunogenicity of the protein. Previously, Ribot et al (19) examined the immunogenicity and protective efficacy of isoforms of rPA that differed in deamidation levels (18,19). The two isoforms compared in that study exhibited comparable immunogenicity and protective immunity; however, the difference in the extent of deamidation between the two isoforms used in that study was minimal, as judged by the incremental difference in charge between the two isoforms (18,19).…”
mentioning
confidence: 97%
“…Previously, others have demonstrated that certain Asn residues within rPA deamidate on a time scale relevant to vaccine dating periods (17,18). In a comprehensive study, Powell et al (18) detected measurable deamidation of 7 of the 68 Asn residues of rPA that had been subjected to conditions conducive to deamidation.…”
mentioning
confidence: 99%
See 2 more Smart Citations